PATRON AND CLIENT IN SMALL TEMPE –TAHU INDSUSTRIES IN BITUNG CITY - Lamadirisi, Maryam; Marlian, Wadjidi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to describe the working relationship between employers and home industry Tempe-Tahu workers in the city of Bitung. The method used in this study is a qualitative approach by collecting data through observation, interviews and documentation studies. The results found in this study were employers from Java and Bitung workers (Sanger, Gorontalo, and Minahasa) who had good working relationships because they felt like their brothers. Salary payments are made by agreement between the employer and the worker (according to the UMR of Bitung city and other prizes). This study recommends that in the work of home industries, especially authentic foods from Java can be accepted by the people of the city of Bitung.